South Pacific paradise rewritten - Lovensheimer, Jim (Oxford ; New York Oxford University Press, 2010)
This book explores the show's complex messages and demonstrates how the presentation of those messages changed throughout the creative process. Jim Lovensheimer shows how Rodgers and especially Hammerstein continually refined and softened the theme of racial intolerance until it was more acceptable to mainstream Broadway audiences. -- [book jacket].
Who can explain it? -- The musical is the message -- An adaptable source : Michener's Tales of the South Pacific -- False starts : The disappearance of Bill Harbison and Dinah Culbert -- You've got to be carefully rewritten : the distillation of racial intolerance -- Nellie and the boys : situating gender in South Pacific -- Culture clash : colonialism and South Pacific -- Still dreaming of paradise.
Includes bibliographical references ([241]-245) and index ([247]-266).
Keywords: Rodgers, Richard -- 1902-1979.; Hammerstein, Oscar -- 1895-1960.; Musicals -- United States -- 20th century -- History and criticism